Does the temperature of –80 °C preserve the activity of antioxidant enzymes embedded into alginate microcapsules? - Khala, Iryna; Repina, Svitlana; Nardid, Oleg; Naumenko, Yevgenia; Mangasarov, Dmytro (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(1):46–49